Controlled Valence Electron Concentration Approach to Tailor the Microstructure and Phase Stability of an Entropy-Enhanced AlCoCrFeNi Alloy - Oh, Min Chul; Lee, Hansung; Sharma, Ashutosh; Ahn, Byungmin (Metallurgical and Materials Transactions A: Physical Metallurgy and Materials Science, 2022)
In this study, the alloying and phase separation behaviors of AlCoCrFeNi-based high-entropy alloys (HEAs) were investigated. The valence electron concentration (VEC) of the AlCoCrFeNi HEA was modified by adding specific elements (Mg, Ti, Mn, Cu, and Zn) to produce biphasic HEAs. These HEAs were prepared by mechanical alloying for 30 hours, followed by the consolidation of the powders at 1000 °C. The results demonstrated the formation of a body-centered cubic (ordered BCC/B2) phase in AlCoCrFeNi–Mg and AlCoCrFeNi–Ti, while a dual-phase face-centered cubic (FCC) phase and minor BCC phases were observed in AlCoCrFeNi–Cu and AlCoCrFeNi–Zn. AlCoCrFeNi and AlCoCrFeNi–Mn exhibited the precipitation of a σ phase in the BCC matrix and a minor FCC phase. The AlCoCrFeNi–Mn HEA exhibited the highest compressive strength among itself, AlCoCrFeNi–Cu, and AlCoCrFeNi–Zn HEAs, owing to the precipitation of a harder σ phase and a higher ordered BCC/B2 fraction. In addition, the AlCoCrFeNi–Cu and AlCoCrFeNi–Zn HEAs exhibited the maximum fracture strain and absorption energies. We propose that a controlled VEC approach by the addition of suitable elements can be used to tailor the microstructure and phase stability of AlCoCrFeNi HEAs.
Keywords: B2 phase; BCC phase; Body-centred cubic; Dual phase; Dual phasis; Face-centered cubic phasis; High entropy alloys; matrix; Phase separation behavior; Valence electron concentration